Mucosal IgA response in the colon against pneinnococcal polysaccharide antigen - Marsetyawan HNE Soesatyo, Marsetyawan HNE Soesatyo (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 1994)
The humoral IgA response to bacterial polysaccharide antigen in rats was investigated in vivo. Rats were immunized with pneumococcal polysaccharide type-3 (PPS-3) via different routes, i.e. in the Peyers patch (iPP), in the colon (I.C.), peritoneal cavity (LP.), and intravenous (I.V.). The development of specific antibody-forming cells (AFC) and their isotypes in the intestinal mucosa, gut-associated lymphoid tissue. (GALT), mesenteric lymph nodes (MLN) and spleen were studied by immunohistochemistry. The serum antibody levels were measured by enzyme-linked " lll unosorbent assay (ELISA).The results showed that iPP immunization evoked high numbers of anti-PPS-3 AFC of the IgA isotype in the mucosa of the small intestine and in the Peyers patch. On the contrary, the I.C. route did not elicit a mucosal response, though a few AFC were found in the MLN and spleen. Following I.P. priming, a specific IgA response was found, especially in the MLN and spleen, and low response was detected in the villi. A high response was found in the parathymic lymph nodes (PTLN). The I.V. immunization gave rise to the development of AFC in the spleen. particularly of the 1gM isotype. There was no mucosal responses to PPS-3 antigen in the colon arise irrespective of the route of immunization.Key-words : IgA-colon-antibody-forming cells- pneumococcal polysaccharide antigen -immunohistochemistry